Credit Sales Accounting System At Pt. Xyz In Bekasi - Titik Purwaningtyas; Hamizar; Taty Noorhayati; Ariska Mediati (JACTA: Journal of Accounting and Tax, 2024)
The purpose of this research was to determine the flow of the credit sales system at PT. XYX in Bekasi and to know the internal control of credit sales at PT. XYZ in Bekasi.This research method uses a qualitative descriptive method, namely a method that uses a natural setting with the intention of interpreting the phenomena that occur and is carried out by involving various existing methods through literature studies, interviews, and analyzing data obtained from companies. Based on the observations it can be concluded that the credit sales system at PT. XYZ in Bekasi runs computerized. There are several things that are not in accordance with internal control according to Mulyadi's theory. There are still several sections that need separation, such as the PPIC section which must be separated from the warehouse section and the separation between the credit section, the receivable collection section, and the accounting section.